Respuesta :

24)

= (25 x 10^7) + (3.8 x 10^7)

= (25 + 3.8) x 10^7

= 28.8 x 10^7

= 2.88  x 10^8

25)

= (670 x 10^2) - (6.1 x 10^2)

= (670 - 6.1) x 10^2

= 663.9 x 10^2

= 6.639 x 10^4

26)

= (3.2 + 5.4) x 10^3

= 8.6 x 10^3

27)

=(15 x 10^26) - (1.4 x 10^26)

= (15 - 1.4) x 10^26

= 13.6 x 10^26

= 1.36 x 10^27

28)

(1.72 x 10^4) + (8 x 10^6)

= (1.72 x 10^4) + (800 x 10^4)

= 801.72 x 10^4

= 8.0172 x 10^6

I don't agree with his answer 9.72 x 10^10. When adding or subtracting in scientific notations, the exponents must be the same so you can use the distributive property, then add or subtract the new coefficients



ACCESS MORE